2006
DOI: 10.1074/jbc.m512621200
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation Affects the Molecular Organization and Stability of E-cadherin Junctions

Abstract: Epithelial cell-cell adhesion is mediated by E-cadherin, an intercellular N-glycoprotein adhesion receptor that functions in the assembly of multiprotein complexes anchored to the actin cytoskeleton named adherens junctions (AJs). E-cadherin ectodomains 4 and 5 contain three potential N-glycan addition sites, although their significance in AJ stability is unclear. Here we show that sparse cells lacking stable AJs produced E-cadherin that was extensively modified with complex N-glycans. In contrast, dense cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
149
5
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(167 citation statements)
references
References 50 publications
12
149
5
1
Order By: Relevance
“…However, the modification of E-cadherin with complex N-glycans has been associated with the formation of dynamic, but weak, adherens junctions, whereas E-cadherin modified by high mannose or less N-glycans has been reported to promote the establishment of stable adherens junctions (33). In light of the report showing the importance of ectodomains of E-cadherin in homophilic adhesion, it is tempting to speculate that these N-glycans affect the interactions between the ectodomains through stearic hindrance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the modification of E-cadherin with complex N-glycans has been associated with the formation of dynamic, but weak, adherens junctions, whereas E-cadherin modified by high mannose or less N-glycans has been reported to promote the establishment of stable adherens junctions (33). In light of the report showing the importance of ectodomains of E-cadherin in homophilic adhesion, it is tempting to speculate that these N-glycans affect the interactions between the ectodomains through stearic hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that alterations in N-glycosylation could modulate cadherin-dependent cell-cell adhesion (19,(31)(32)(33). Taniguchi and co-workers (19) reported that overexpression of GnT-III enhanced cell-cell adhesion in B16 melanoma cells, because of a delay in the turnover of E-cadherin on the cell surface.…”
Section: Gnt-iii Expression Prolonged E-cadherin Turnover On Cell Surmentioning
confidence: 99%
“…Cytoplasmic O-glycosylation of the E-cadherin cytosolic tail has been shown to occur in response to endoplasmic reticulum stress and inactivate Ecadherin-mediated intercellular adhesion by preventing its transport to the cell membrane [50]. In addition, E-cadherin can be N-glycosylated and the N-glycosylation at Asn-633 is essential for E-cadherin expression, folding and trafficking [51,52]. In an earlier study, Yoshimura, et al reported that E-cadherin-mediated cell adhesion was regulated by GnT-III.…”
Section: A Mutual Regulation Between Gnt-iii Expression and E-cadherimentioning
confidence: 99%
“…However, the modification of E-cadherin with complex N-glycans has been associated with the formation of dynamic, but weak, adherens-junctions, whereas E-cadherin modified by high mannose or less N-glycans has been reported to promote the establishment of stable adherensjunctions [51]. In addition, Pihno, et al reported that Ecadherin underwent extensive modification of its N-glycans with β1-6 branched and sialylated structures during acquisition of the malignant phenotype in a canine mammary tumor cell line model [64].…”
Section: A Mutual Regulation Between Gnt-iii Expression and E-cadherimentioning
confidence: 99%
“…In turn, canonical Wnt activates DPAGT1 expression via ␤-catenin at a transcriptional level. Furthermore, N-glycosylation inhibits E-cadherin adhesion and interferes with E-cadherin antagonism of canonical Wnt signaling (17,18). Aberrant activation of canonical Wnt and N-glycosylation pathways has been associated with tumorigenesis (9, 19 -21).…”
mentioning
confidence: 99%